Knowledge and beliefs about malaria transmission and practices for vector control in Southern Mexico - Rodríguez Américo David; Penilla Rosa Patricia; Henry-Rodríguez Mario; Hemingway Janet; Betanzos Angel Francisco; Hernández-Avila Juan Eugenio (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To investigate the knowledge and beliefs about malaria transmission and practices for vector control in eight villages on the coastal plain of Chiapas, Mexico. MATERIAL AND METHODS: A cross-sectional survey was conducted during May and June 1995 in Chiapas, Mexico. A questionnaire to investigate family structure, knowledge on malaria transmission, preventive measures and attitudes towards seeking treatment was applied to both family heads of a sample of households. Associations were analyzed by estimating odds ratios with confidence intervals and p values, using bivariate and multivariate logistic regression methods. RESULTS: Malaria knowledge was poor and only 48% associated malaria with mosquito bites. The perceived benefit of indoor residual spraying was associated to a reduction of mosquitoes, a reduction in the numbers of cockroaches and rats, but only 3% associated it directly with the prevention of malaria transmission. Most villagers (97.6%) agreed with the indoor residual spraying of insecticides. Ninety nine percent of villagers had mosquito bednets, 75.7% used them all year round. Other measures used by villagers to prevent mosquito bites were smoke and mosquito coils. Above 40% of villagers self-medicated when any member of the family had a fever episode, but 51% attended proper health services (community dispensary, private physician, health worker). About 61% used pesticides for agricultural or livestock purposes and 55% applied them themselves. Women had a greater participation as family health promoters, with 70% of the housewives being in charge of the application of self-protection preventive measures. CONCLUSIONS: Educational programs aimed at increasing awareness on the participation of mosquitoes on malaria transmission could promote community participation in malaria control in the region.